Measurement of Cochlear Implant Electrode Position From Intraoperative Post-insertion Skull Radiographs: A Validation Study. Issue 9 (October 2015) - Svrakic, Maja; Friedmann, David R.; Berman, Phillip M.; Davis, Adam J.; Roland, J. Thomas; Svirsky, Mario A.
Abstract : Objective: To validate a method of measuring angular depth of insertion (aDOI) as well as positional depth of each electrode contact in a cochlear implant by using intraoperative postinsertion skull radiographs. Study Design: Retrospective review. Setting: Tertiary referral center. Patients: Intraoperative postinsertion radiographs obtained from 18 cochlear implant recipients were chosen for analysis. One high-resolution computer tomography scan of the head with the electrode in place was also analyzed. One cadaveric temporal bone with an inserted electrode provided additional data for analysis. Intervention: aDOI and position of each electrode contact were measured from the radiographs using readily available software. High-resolution computer tomography imaging of the cochlea and electrode were reconstructed in three dimensions and used to simulate head rotation during intraoperative radiographs. The cadaveric temporal bone was imaged by x-ray at various acquisition angles. Main Outcome Measures: We evaluated the error introduced in measuring aDOI by assessing intra- and inter-rater variability. We also evaluated the error introduced by x-ray acquisition at nonstandardized angles by analyzing the three-dimensional construct and the cadaveric temporal bone. Results: The concordance correlation coefficients for intrarater (0.991) and inter-rater (0.996) variability in aDOI measurement were excellent. The error introduced by nonstandardized x-ray acquisition angles was only −12.5 degrees to +15.8 degrees even at the limits of clinically relevant head rotation. Conclusions: The intraoperative postinsertion radiograph is sufficient for estimating positional depth of electrode contacts and the aDOI. This measure is robust in the face of nonstandardized x-ray acquisition angles, and shows good intra- and inter-rater variability